The Inverse Fresnel Beam XSP-CDP Stack Imaging in Crosswell Seismic - Yang, Fei-Long; Ren, Guang-Ying; Yao, Feng-Ming; Zhao, Chong (Frontiers in Earth Science, 2022)
In order to overcome the shortcomings of serious arc drawing and low computational efficiency in crosswell seismic migration method and the problems of inaccurate velocity model and sparse distribution of reflection points in traditional stack imaging method, the paper proposes an inverse Fresnel beam XSP-CDP stack imaging method based on first-arrival wave velocity tomography combined with the characteristics of crosswell seismic wave field. Firstly, an accurate crosswell velocity model is established by first-arrival wave tomography inversion method based on the characteristics of high energy and easy pick-up of first-arrival wave in crosswell seismic. Secondly, the velocity model is optimized and the energy contribution weights of effective rays to the receiver point are calculated through the crosswell seismic Fresnel beam wavefield forward numerical simulation method. Then, the reflected wavefield is dynamically migrated to the reflection points within the first Fresnel zone according to the weight function, and the intensive common reflection point(CRP) gather after normal moveout(NMO) correction is generated. Finally, an appropriate bin is selected for stacking. In this paper, the inverse Fresnel beam method is used to decompose the single-channel seismic wavefield into the effective reflection points in the Fresnel zone, which makes the fold number of the reflection point more uniform and improves the imaging accuracy. Model test and actual data processing results proved the validity and robust of this method.